Do Magnet®-Designated Hospitals Perform Better on Medicare's Value-Based Purchasing Program?. (July 2020) - Spaulding, Aaron; Hamadi, Hanadi; Moody, LaRee; Lentz, Luanne; Liu, Xinliang (Albert); Wu, Yu (Janet)
Abstract : OBJECTIVE: The aim of this study was to explore the relationship between a hospital's Magnet ® recognition status, tenure, and its performance in the Hospital Value-Based Purchasing (HVBP) program. BACKGROUND: Previous studies have sought to determine associations between quality of care provided in inpatient setting and the Magnet Recognition Program ® ; however, no study has done so using the most recent (FY2017) iteration of the HVBP program, nor determined the influence a hospital's Magnet designation tenure has on HVBP scores. METHOD: This study used a cross-sectional study design of 2686 hospitals using propensity score matching to reduce bias and improve comparability. RESULTS: Magnet-designated hospitals were associated with higher total performance, process of care and patient experience of care scores, and lower efficiency score. No association was identified between the length of time hospitals have been Magnet designated. CONCLUSION: Findings suggest non-Magnet status hospitals need to consider implementing the principles of Magnet into their culture or participation in the Magnet Recognition Program to provide higher quality of care. Abstract : Supplemental digital content is available in the text.